Single-cell RNA sequencing reveals the critical role of alternative splicing in cattle testicular spermatagonia - Xiuge Wang; Chunhong Yang; Xiaochao Wei; Yaran Zhang; Yao Xiao; Jinpeng Wang; Qiang Jiang; Zhihua Ju; Yaping Gao; Yanqin Li; Yundong Gao; Jinming Huang (Biology Direct)
Abstract Spermatogonial stem cells (SSCs) form haploid gametes through the precisely regulated process of spermatogenesis. Within the testis, SSCs undergo self-renewal through mitosis, differentiation, and then enter meiosis to generate mature spermatids. This study utilized single-cell RNA sequencing on 26,888 testicular cells obtained from five Holstein bull testes, revealing the presence of five distinct germ cell types and eight somatic cell types in cattle testes. Gene expression profiling and enrichment analysis were utilized to uncover the varied functional roles of different cell types involved in cattle spermatogenesis. Additionally, unique gene markers specific to each testicular cell type were identified. Moreover, differentially expressed genes in spermatogonia exhibited notable enrichment in GO terms and KEGG pathway linked to alternative splicing. Notably, our study has shown that the activity of the YY1 regulation displays distinct expression patterns in spermatogonia, specifically targeting spliceosome proteins including RBM39, HNRNPA2B1, HNRNPH3, CPSF1, PCBP1, SRRM1, and SRRM2, which play essential roles in mRNA splicing. These results emphasize the importance of mRNA processing in spermatogonia within cattle testes, providing a basis for further investigation into their involvement in spermatogonial development.